A potential role for the interaction of Wolbachia surface proteins with the Brugia malayi glycolytic enzymes and cytoskeleton in maintenance of endosymbiosis. - Elena Melnikow; Shulin Xu; Jing Liu; Aaron J Bell; Elodie Ghedin; Thomas R Unnasch; Sara Lustigman (Public Library of Science (PLoS), 2013)
The human filarial parasite Brugia malayi harbors an endosymbiotic bacterium of the genus Wolbachia. The Wolbachia represent an attractive target for the control of filarial induced disease as elimination of the bacteria affects molting, reproduction and survival of the worms. The molecular basis for the symbiotic relationship between Wolbachia and their filarial hosts has yet to be elucidated. To identify proteins involved in this process, we focused on the Wolbachia surface proteins (WSPs), which are known to be involved in bacteria-host interactions in other bacterial systems. Two WSP-like proteins (wBm0152 and wBm0432) were localized to various host tissues of the B. malayi female adult worms and are present in the excretory/secretory products of the worms. We provide evidence that both of these proteins bind specifically to B. malayi crude protein extracts and to individual filarial proteins to create functional complexes. The wBm0432 interacts with several key enzymes involved in the host glycolytic pathway, including aldolase and enolase. The wBm0152 interacts with the host cytoskeletal proteins actin and tubulin. We also show these interactions in vitro and have verified that wBm0432 and B. malayi aldolase, as well as wBm0152 and B. malayi actin, co-localize to the vacuole surrounding Wolbachia. We propose that both WSP protein complexes interact with each other via the aldolase-actin link and/or via the possible interaction between the host's enolase and the cytoskeleton, and play a role in Wolbachia distribution during worm growth and embryogenesis.